1965
DOI: 10.2466/pms.1965.21.1.275
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Eidetic Imagery among the Retarded

Abstract: Since Haber and Haber had recently established the fact that eidetic imagery (EI) is not a common phenomenon among normal American children, this study was based upon the premise that it may be an abnormal phenomenon, more likely to be found among retarded children. It was reasoned that the prolonged retention of a primitive form of cognition (typified by EI) should be a more likely component of a generally retarded rate of conceptual and language development. This prediction was tested by administering Haber'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

1972
1972
1985
1985

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The Latin version of his treatise appeared in 1572 at Basel as Oprical Thesaurus. The only modem notice of his awareness of eidetic imagery is by Siipola and Hayden (1965). Neither Bauer (191 1) nor Omar (1977) mentioned eidetic studies.…”
Section: Eidetic Imagerymentioning
confidence: 93%
See 1 more Smart Citation
“…The Latin version of his treatise appeared in 1572 at Basel as Oprical Thesaurus. The only modem notice of his awareness of eidetic imagery is by Siipola and Hayden (1965). Neither Bauer (191 1) nor Omar (1977) mentioned eidetic studies.…”
Section: Eidetic Imagerymentioning
confidence: 93%
“…A possible exception may be the work by Siipola and Hayden (1965) on eidetic imagery among retarded and brain-injured subjects. Their results relate to the theory of Jaensch (1923) about the early layering (Schichtenbildung) of human consciousness.…”
Section: Eidetic Imagerymentioning
confidence: 94%
“…According to Siipola & Hayden (1965), the rate increases to 50% for children with brain injury, though Richardson & Cant (1970) . have presented contradictory data.…”
mentioning
confidence: 99%
“…4 In addition, the frequencies f ound for retarded children are inconsistent from study to study (cf. Siipola &Hayden, 1965, andRichardson &Cant, 1970).…”
mentioning
confidence: 99%
“…In the general population, the frequency of children's possessing eidetic ability varies with the study (i.e., 8 to 50%) (Haber, 1969;Gummerman et al, 1972;Siipola and Hayden, 1965). Pierro (1967) found that good spellers are good eidetic imagers, but there were no sex differ ences.…”
Section: Eidetic Imagerymentioning
confidence: 99%